Relevance of shari’ah governance in driving performance of Islamic Banks during the financial crisis: international evidence - Nomran, Naji Mansour; Haron, Razali (IntechOpen, 2020)
This study aims to examine the impact of Shari’ah governance mechanism on the performance of Islamic banks (IBs) during the financial crisis of 2008. Data were collected from 66 IBs over 18 countries covering the period of 2007–2015 and analyzed using the System-GMM estimator. The findings indicate that an increase in SSB effectiveness increases IBs’ performance even during the crisis periods. A possible justification for this positive effect is related to the SG structure of IBs that allows them to undertake higher risks to achieve a high efficiency level. For this, the IBs, policymakers and practitioners should consider these findings when aiming to improve SG practices in the Islamic banking industry, which in turn may help in protecting IBs during crisis and non-crisis periods. More specifically, they should give due importance to SSB (size, cross-membership, educational qualification, reputation and expertise) in enhancing the performance of IBs during the crisis and non-crisis periods. This study provides additional evidence on how IBs can sustain their performance during either crisis or non-crisis periods through adopting appropriate SG structure. However, the study only focuses on a small sample of 66 IBs due to lack of the data.